A study on the temporal patterns, anatomical distribution, and influencing factors of radiation therapy-associated second primary cancers in gynecological malignancies - Ye, Yuling; Li, Xiuhua; Lin, Ting; Lin, Xian; Ke, Hongqian; Wu, Hongqing; Sun, Yang (Frontiers in Oncology, 2026)
ObjectiveTo systematically analyze the clinical characteristics of post-radiotherapy secondary primary cancers (SPC) after treatment for gynecological malignancies, with the aim of informing and optimizing tumor management strategies.MethodsA retrospective collection of clinical data for 36 patients with gynecological malignancies who underwent radiotherapy at our hospital from January 2004 to December 2021.ResultsThe first primary cancer was predominantly cervical cancer (31 cases, 86.1%), with endometrial cancer accounting for 5 cases. Radiotherapy-related variables included the median radiotherapy duration of 42.5 days, external irradiation dose of 49.375 Gy, and total dose of 69.5 Gy; FIGO stages I/II/III were 7/18/11; lymph node metastasis in 6 cases; HPV positive in 20 cases; surgical history in 18 cases and chemotherapy history in 30 cases. The SPC cohort had a median onset age of 58 years and a median interval of 8 years after radiotherapy, with primary sites mostly in the rectum/colon and uterus; 24 cases occurred outside the radiotherapy field. Surgical, radiotherapy, and chemotherapy histories all influenced the timing and site of SPC. The median onset age after radiotherapy and interval to SPC were significantly longer in the cervical cancer group than in the endometrial cancer group (P = 0.01), and most SPC occurred within 5–10 years.ConclusionsThe pathological features and treatment history of the initial cancer were associated with the timing and location of SPC. Analyses of post-radiotherapy SPC characteristics provide a scientific basis for optimizing clinical management and reducing SPC risk.